Four-year follow-up of corneal aberrations and visual functions of myopic patients after laser in situ keratomileusis - Liu, Tai-Xiang (Pak J Med Sci, 2015)
OBJECTIVE: To report on 4-year follow-up of corneal higher-order aberrations and daily visual functions of myopic patients after laser in situ keratomileusis (LASIK). METHODS: One hundred thirty four eyes of 67 patients who underwent LASIK guided by aspherical ablation were included in this study. The vision, corneal spherical aberration (SphA) and Coma were recorded before LASIK and at 6 month and 4 year after LASIK. The evaluation of the questionnaire about daily visual functions was performed by the same physician after LASIK. RESULTS: No eye decreased the BCVA during 4 year follow-up. The effect index and safety index were 1.08±0.16, 1.11±0.17 and 1.12±0.16, 1.13±0.14 respectively at 6 month and 4 year post-LASIK. After LASIK the corneal SphA and Coma were significantly increased, however the difference between 6 month and 4 year post-LASIK was no statistical significance. Most patients (94.3%-92.4%) felt satisfaction or high satisfaction about the ability to perform each daily visual function after LASIK. Meanwhile there was still about 7.4%-9.2% patients who complained that they could not drive at night. Further analysis showed that the score of driving at night was negative correlation with corneal SphA (r=-0.645, p=0.040; r=-0.688, p=0.040 at 6 month and 4 year post-LASIK respectively). CONCLUSIONS: Our four-year follow-up outcomes indicated that the myopic patients after LASIK had the long-term stable corneal aberration and satisfaction of daily visual functions.